PERSONNEL AUDIT AND HR ANALYTICS AS TOOLS FOR EFFECTIVE HUMAN RESOURCE MANAGEMENT IN AN ORGANIZATION (Regional aspects of productive forces development of Ukraine, 2024)
ABSTRACTIntroduction. The article examines the features and relationship between personnel audit and HRanalytics as key tools for effective human resource management in modern organizations. The need tointegrate these tools to increase the effectiveness of personnel management and the adaptability oforganizations to the challenges of a dynamic business environment is substantiated. The relevance ofcombining personnel audit and HR analytics is highlighted in order to form a sustainable, flexible andeffective personnel management system capable of responding promptly to changes in the internal andexternal environment.Main content. The article defines the essence of personnel audit, its main stages, tasks andmethods aimed at assessing the effectiveness of the personnel management system, identifying problemareas and developing recommendations for their elimination. HR analytics is analyzed in detail as aninnovative tool based on the analysis of personnel data for making informed management decisions,forecasting personnel processes and developing human capital development strategies. A comparativeanalysis of personnel audit and HR analytics was conducted, outlining their common features,differences, and opportunities for effective combination.Particular attention is paid to the practical significance of integrating personnel audit and HRanalytics. It is proven that the use of these tools in combination allows organizations not only to carry outan objective assessment of the state of the personnel management system, but also to form forecasts thatcontribute to the adoption of strategically balanced decisions. The integration of audit and HR analyticshelps to identify factors that affect the level of motivation, staff turnover, employee satisfaction, and alsohelps to develop effective measures to optimize personnel policy and increase labor productivity.It is noted that the combination of these approaches allows to ensure a high level of transparencyof personnel management processes, reduce risks associated with shortcomings in personnel policy, andincrease the adaptability of organizations to new operating conditions. The scientific novelty of the studylies in the integrated approach to the analysis of the role of personnel audit and HR analytics as  complementary tools of strategic human resources management. The practical significance of the resultsobtained lies in the possibility of their use for the development of an effective personnel strategy aimed atensuring the competitiveness of organizations and achieving their long-term goals.Purpose. To substantiate the advantages of integrating personnel audit and HR analytics to createan adaptive and effective human capital management system.Keywords: personnel audit, HR analytics, personnel management, human capital, personnelmanagement.